Relationships between floods and urban expansion in the Ipiranga Stream Basin - Rodrigues, Thaiane Cardoso; Calixto , Clarisse Machado Chaves; Souza , Geovani Genovez (Technical and Scientific Journal Green Cities, 2024)
The purpose of this article is to reflect on floods and inundations in urban areas exacerbated by demographic growth and real estate developments. The study analyzes the Santa Luzia neighborhood in the municipality of Juiz de Fora as a case study, as its characteristics closely resemble those of various other locations. This work takes the form of a literature review dedicated to the topic, addressing explanations relevant to floods and inundations. The analysis includes considerations about urban growth, a temporal delimitation covering the history of the neighborhood and its surrounding region. Additionally, an investigation of local maps is conducted, complemented by an analysis of the main streams within the Ipiranga watershed from the perspective of canalizations carried out in the 21st century.